Determination of the main solid-state form of albendazole in bulk drug, employing Raman spectroscopy coupled to multivariate analysis - Calvo, Natalia Lorena (2016)
Fil: Fil: Calvo, Natalia Lorena. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Área de Análisis de Medicamentos; Argentina.